ACTIVATED CARBON, BIOCHAR, AND LIGNOCELLULOSIC DERIVATIVE MATERIALS FOR REMOVING ANTIBIOTICS FROM WATER: AN OVERVIEW - Negrete-Vergara, Camila; Sanchez, Julio; Salfate, Gabriel; Oyarce, Estefania; Roa, Karina; Boulett, Andres; Rivas, Bernabé (Journal of the Chilean Chemical Society, 2025)
Antibiotics have improved the quality of life of human society due to their applications in medicine and food production. Nevertheless, antibiotics are also considered emerging pollutants because they have been found in the environment, water sources, and tap water. Their chemical stability and the excessive usage of these substances are the main causes of their presence in the environment. Antibiotics can be removed from water using adsorbent materials, in which activated charcoal has been extensively used for removing organic pollutants. Concerns about the environmental impact of producing activated charcoal are placing the interest in new eco-friendly materials for organic pollutant removal from water such as biochar and lignocellulosic materials. Those materials have desirable properties that allow them to remediate water in the presence of antibiotics. In this study, the use of activated carbon, biochar, and lignocellulosic materials for removing antibiotics from water is reviewed. Here we discuss the advantages and limitations of each material for the aforementioned purpose, comparing their efficiency in the removal of common antibiotics used in healthcare and agroindustry, and considering new approaches and alternatives to the technologies used for antibiotic removal from water.